Guidance for the collection of case report form variables to assess safety in clinical trials of vaccines in pregnancy. Issue 49 (1st December 2016) - Jones, Christine E.; Munoz, Flor M.; Kochhar, Sonali; Vergnano, Stefania; Cutland, Clare L.; Steinhoff, Mark; Black, Steven; Heininger, Ulrich; Bonhoeffer, Jan; Heath, Paul T.
Abstract: Vaccination in pregnancy is an effective strategy to prevent serious infections in mothers and their infants. Safety of this strategy is of principal importance to all stakeholders. As the number of studies assessing safety of vaccines in pregnancy increases, the need to ensure consistent collection and reporting of critical data to allow comparisons and data pooling becomes more important. The Global Alignment of Immunization Safety Assessment in Pregnancy (GAIA) project aims to improve data collection and create a shared understanding of maternal, fetal and neonatal outcomes in order to progress the global agenda for vaccination in pregnancy. The guidance in this document has been developed to harmonize the data collected in case report forms used for safety monitoring in clinical trials of vaccination in pregnant women. Data to be collected is prioritized to allow applicability in diverse research settings, including low and middle-income countries. Standardized data will enable the research community to have a common base upon which to conduct meta-analyses, strengthening the applicability of outcomes to different settings.